PSoC BASED EMBEDDED RF LINK DESIGN - Tasci, Burak; Erol, Yavuz (Ieee, 2020)
In this article, RF link design has been realized by using RF technology with Programmable System on Chip (PSoC). RFM22B transceiver module operating both as a transmitter and a receiver with the modulation techniques such as Frequency-Shift Keying (FSK), Gauss Frequency-Shift Keying (GFSK), and On-Off Keying (OOK) in the 240 to 960 MHz frequency range has been used in the radio frequency communication system. The serial information package required for the communication of RF modules have been provided with a programmable system on the CY8C5868AXI-LP035 chip of Cypress company. In the designed system, the channels in the frequency range from 240 to 960 MHz were generated. Experimental results showed that a secure RF communication was successfully provided by scanning the channels in case of a noise signal thanks to the developed algorithm.
13th International Conference on Communications (COMM) -- JUN 18-20, 2020 -- ELECTR NETWORK
Keywords: PSoC; RF; link; secure communications; channel scanning